2006
DOI: 10.1016/j.intcom.2006.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Cross-cultural differences in recognizing affect from body posture

Abstract: Conveyance and recognition of human emotion and affective expression is influenced by many factors, including culture. Within the user modeling field, it has become increasingly necessary to understand the role affect can play in personalizing interactive interfaces using embodied animated agents. However, little research within the computer science field aims at understanding cultural differences within this vein. Therefore, we conducted a study to evaluate if differences exist in the way various cultures per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
94
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 147 publications
(101 citation statements)
references
References 25 publications
(22 reference statements)
4
94
0
3
Order By: Relevance
“…This vector describes the configuration of the posture in terms of distances between body joints and angles between body segments. Details on the data collection are provided in [10]. The second dataset contains 103 non-acted postures collected in a whole-body computer game scenario.…”
Section: Multi-score Learning On Affective Posture: Resultsmentioning
confidence: 99%
“…This vector describes the configuration of the posture in terms of distances between body joints and angles between body segments. Details on the data collection are provided in [10]. The second dataset contains 103 non-acted postures collected in a whole-body computer game scenario.…”
Section: Multi-score Learning On Affective Posture: Resultsmentioning
confidence: 99%
“…Until recently, the main modality used to measure the affective state of people was their facial expressions [4]. Recent psychology studies, however, have revealed that body expressions are also a very good indicator of affect [e.g., 2,3,10]. These studies encouraged us into researching the possibility to create an automatic recognition system that would use the players' body movement to detect their affective state.…”
Section: Introductionmentioning
confidence: 99%
“…Using acted affective postures, Kleinsmith et al [24] explored cultural differences in expressing and recognizing affect from body expressions. The analysis, based on the set of low-level descriptive features proposed in [24], highlighted some differences between the cultures but showed also the possibility to build automatic recognition models that reflect the recognition of human observers from different cultures.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations